COMSOL simulation of electrostatic confinements in nanoscale TMDC QD devices - Lai, Marcus Kar Fai (Nanyang Technological University, 2021)
Qubits for quantum computer applications can be based on many different types of architectures and operational principles. One possible quantum nanostructure which has been known to allow properties such as spin-readout is Quantum Dots (QD), showing promise as potential future scalable and integrable semiconductor qubit architectures. With certain advantages over highly researched materials such as Gallium Arsenide (GaAs) and Doped crystal structures, Transition Metal Dichalcogenide (TMDC) Quantum Dot (QD) devices recently gained much interest, heavily spurring research efforts towards geometry, fabrication, and characterisation. Devices that have been made, using these 2D materials as 2-Dimensional Electron Gas (2DEG) interfaces, combined with multi-contact lateral electrostatic confinements, show coulomb blockade oscillation and coulomb diamond characteristics from Source-Drain (SD) and Plunger gate (P) voltage sweeps. These are hallmarks of QD formation, having been demonstrated in many different multi-contact geometries. In this investigation, electrostatic COMSOL Multiphysics simulation is tested then applied for a “transistor-like” split-gate geometry. Simultaneously, apparatus for Room Temperature (RT) and 4 Kelvin (4K) electrical characterisation have been reworked. 4K electrical characterisation of a newly fabricated split-gate MoS2 device suggests formation of QDs within the SD-channel. Purely electrostatic simulations weakly suggest evidence for possible QD formation sites. Therefore, this investigation hopes to contribute towards predictive modelling for potential QD formation sites, based on geometric and electrostatic potential simulation. Geometric optimisation attempts are mentioned at the end of this paper.